Chemical-biology approaches to probe DNA and RNA G-quadruplex structures in the genome. Issue 9 (6th January 2020) - Raguseo, Federica; Chowdhury, Souroprobho; Minard, Aisling; Di Antonio, Marco
Abstract : G-quadruplexes are nucleic-acids secondary structures that can be formed under physiological conditions. In this review, we critically present the most relevant chemical-biology methods to probe the biological functions of G-quadruplex structures. Abstract : G-quadruplexes are nucleic acids secondary structures that can be formed in guanine-rich sequences. More than 30 years ago, their formation was first observed in telomeric DNA. Since then, a number of other sequences capable of forming G-quadruplex structures have been described and increasing evidence supporting their formation in the context of living cells has been accumulated. To fully underpin the biological significance of G-quadruplexes and their potential as therapeutic targets, several chemical-biology tools and methods have been developed to map and visualise these nucleic acids secondary structures in human cells. In this review, we critically present the most relevant methods developed to investigate G-quadruplex prevalence in human cells and to study their biological functions, presenting the next key chemical-biology challenges that need to be addressed to fully unravel G-quadruplex mediated biology and their therapeutic potential.